PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN CV. WAHYU ILLAHI - HANE JOHAN, SE. MM (Menara Ilmu, 2016)
The background of this research is a gap in the provision of the compensation receivedis not in accordance with the demands of fulfillment and satisfaction. Including the growingneed for consumption that contributes to the high economic inflsi community in meeting theeconomic needs that are not balanced with the income level of employees receive wagesearned, including various types of compensation in CV. Wahyu Illahi. The number ofcomplaints and dissatisfaction over the compensation received by the employee, the direct orindirect impact on the process of work activities, which affect the implementation activities ofdaily work because employees are not motivated in running the work activities, as a result ofcompensation received can not fix income and welfare of employees.It can be seen from the coefficient of determination or R square is 0, 406 which meansthat the contribution of compensation for the performance of employees amounted to 0.406 or.40.6% and is influenced by other variables (100% - .. 40.6%) was up 59.4% variables notexamined in this study. Based on the results obtained regression coefficient: Y = 14.00 + 0.589can be explained that every increase in the compensation of one unit will increase the value ofthe employee's performance of 0.589 units or reverse any decline in the compensationamounted to 0.589 units. Sedangakan when no addition and subtraction of the compensationthe employee's performance will remain at 14:00 unit.Keywords: Compensation Effect on Employee Performance